2011
DOI: 10.1111/j.1758-2229.2010.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Pseudomonas putida at low temperature: global transcriptomic and proteomic analyses

Abstract: In its natural habitats (soil, water and rhizosphere), Pseudomonas putida can suffer frequent and long-term changes in temperature that affect its growth and survival. Pseudomonas putida KT2440, a well-characterized model strain, grows optimally at 30°C but can proliferate at temperatures as low as 4°C. However, little information is available on the physiological changes that occur when P. putida grows at low temperatures. To investigate this area, the transcriptome and proteome profiles of cells exponentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 95 publications
6
61
0
Order By: Relevance
“…Hence, the optimum temperature of our test bacterial strain of Pseudomonas putida (SUBP03) was recorded to be 30 °C. Present finding is quite consistent with the earlier studies where P. putida has been noticed to exhibit highest growth at 30 °C too (3)(4)(5).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, the optimum temperature of our test bacterial strain of Pseudomonas putida (SUBP03) was recorded to be 30 °C. Present finding is quite consistent with the earlier studies where P. putida has been noticed to exhibit highest growth at 30 °C too (3)(4)(5).…”
Section: Resultssupporting
confidence: 93%
“…. Notably, bacteria were found to utilize unified strategies to deal with the environmental stress (3)(4)(5)(24)(25)(26). Nevertheless, several studies apparently suggested the expression of the global molecular chaperones, which maintain the cellular homeostasis, including rpoE, rpoS and rpoH genes in E. coli; dnaK, dnaJ, and grpE in Pseudomonas spp.…”
Section: Influence Of Temperature On the Growth Of Pseudomonas Putidamentioning
confidence: 99%
“…Many of these changes in gene expression are presumably oriented toward overcoming the challenges imposed by cold shock. Studies aimed at characterizing the cold shock responses of other organisms have commonly identified a number of genes involved in DNA modulation, transport and binding functions, membrane fluidity, cell envelope modification, and energy metabolism (16,(58)(59)(60)(61)(62)(63). We found similar genes that exhibited differential expression upon a low-temperature shift in V. cholerae as well (Table S1).…”
Section: Discussionsupporting
confidence: 54%
“…These processes were done aseptically inside a biosafety cabinet, as well in according to standard. It was indicated that multiple loops seeding ensure proper bacterial growth [3]. The orbital shaker was operated at 37℃ and 180 rpm.…”
Section: Strain and Cultivationmentioning
confidence: 99%
“…Upon inoculation into a suitable media, this gram negative, aerobic and gammaproteo bacterium selectively takes up nutrients from the medium for biosynthesis [3]. The initial lag growth phase is a period of cell change in accordance with the new environment.…”
Section: Introductionmentioning
confidence: 99%